Komunikasi terapeutik dalam keperawatan kardiovaskular: Sebuah tinjauan sistematis dan meta analisis hasil fisiologis dan psikologis - Muhammad Iqbal; Debie Dahlia (Holistik Jurnal Kesehatan, 2026)
Background: Cardiovascular nursing practice often prioritizes mechanical hemodynamic monitoring while neglecting interpersonal engagement. Qualitative findings support the value of therapeutic communication; however, there remains a lack of quantitative synthesis regarding its effect size on physiological stability. Purpose: To measure the impact of therapeutic communication on cardiac anxiety and heart rate variability (HRV) Method: This literature review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The article search was designed using the PICOS framework: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study). The literature search was conducted in PubMed, Scopus, and CINAHL using the keywords “therapeutic communication” AND “nurse-patient communication” AND “cardiovascular patients” AND “cardiac anxiety” AND “heart rate variability” AND “psychological outcomes” AND “physiological outcomes.” The publication timeframe was from 2020 to 2026, and the search included articles in both English and Indonesian. The search yielded 15 relevant and usable articles. Results: The study demonstrated a significant reduction in cardiac anxiety (SMD = -0.89, 95% CI -1.15 to 0.63) alongside a significant improvement in physiological indicators. The observed heterogeneity (I²) of 83% was primarily attributed to cultural and environmental moderators. Conclusion: Therapeutic communication serves as a highly promising clinical intervention equivalent to adjunctive pharmacological stabilization, effectively reducing the cardiotoxic effects of increased sympathetic activity.   Keywords: Anxiety; Cardiovascular Nursing; Heart Diseases; Therapeutic Communication.